2015
DOI: 10.4236/lce.2015.61001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sustainable Energy Systems in Ecovillages: A Review of Progress in BedZED and Masdar City

Abstract: This paper explores sustainable energy systems in ecovillages based on the concept of the Zero Energy Building. The cases discussed in this paper include BedZED in the United Kingdom and Masdar City in the Middle East. These two communities contain features characterized by the sustainable principles of the ecovillage concept by using renewable energy and reclaimed materials to reach a low/zero energy system in buildings. The creation of more ecovillages and the growth of current ecovillages play an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…CE initiatives may comprise communities of place-emphasizing shared values associated with a particular territory or landscape-or communities of practice-emphasizing shared ethics and world views, financial circumstances or problems (Magnani and Osti, 2016; but see also Becker and Kunze, 2014) Energy cooperatives (REScoops) are the oldest, and perhaps best known, type of CE; these may be either energy producers, suppliers, or both (Capellán-Pérez et al, 2016;Magnani and Osti, 2016), and provide energy or revenue from sales to their members, who are not necessarily part of the same geographical community. Other types of initiatives include community development companies or not-for-profit organizations who manage production or supply for direct local benefit (Slee and Harnmeijer, 2017;Harnmeijer et al, 2018), and sustainability movements of various sorts ranging from substantial and well-organized transition towns initiatives (Seyfang and Haxeltine, 2012) to eco-villages and informal citizen's groups emphasizing self-sufficiency and energy saving (Georg, 1999;Zhu et al, 2015;Renau, 2018). However, as Creamer et al (2018) have observed, CE refers to a broad spectrum of energy-related initiatives, not a specific class of project.…”
Section: Community Energymentioning
confidence: 99%
“…CE initiatives may comprise communities of place-emphasizing shared values associated with a particular territory or landscape-or communities of practice-emphasizing shared ethics and world views, financial circumstances or problems (Magnani and Osti, 2016; but see also Becker and Kunze, 2014) Energy cooperatives (REScoops) are the oldest, and perhaps best known, type of CE; these may be either energy producers, suppliers, or both (Capellán-Pérez et al, 2016;Magnani and Osti, 2016), and provide energy or revenue from sales to their members, who are not necessarily part of the same geographical community. Other types of initiatives include community development companies or not-for-profit organizations who manage production or supply for direct local benefit (Slee and Harnmeijer, 2017;Harnmeijer et al, 2018), and sustainability movements of various sorts ranging from substantial and well-organized transition towns initiatives (Seyfang and Haxeltine, 2012) to eco-villages and informal citizen's groups emphasizing self-sufficiency and energy saving (Georg, 1999;Zhu et al, 2015;Renau, 2018). However, as Creamer et al (2018) have observed, CE refers to a broad spectrum of energy-related initiatives, not a specific class of project.…”
Section: Community Energymentioning
confidence: 99%
“…The project was completed in 2002 and is located in Hackbridge, London. BedZED community was designed by Bill Duster Architects in collaboration with the Peabody Trust (client) and Bioregional Development Group (environmental consultants) [119]. The project's size is 1.7 hectares (ha), with 116 dwellings per hectare, including live/work units [112,114,120,121].…”
Section: Beddington Zero Energy Development (Bedzed) Londonmentioning
confidence: 99%
“…The project aimed to cover emissions from office and local energy use, embodied energy from construction, transports, food, and waste [114]. An 81% reduction in energy use for hot water (5.2 kWh/person/day) and a 45% reduction in electricity use (3.4 kWh/person/day) was reported, compared to the average in Sutton, London [114,119,120].…”
Section: Beddington Zero Energy Development (Bedzed) Londonmentioning
confidence: 99%
“…Energy cooperatives (REScoops) are the oldest, and perhaps best known, type of CE; these may be either energy producers, suppliers, or both (Magnani andOsti 2016, Capellán-Peréz et al 2016), and provide energy or revenue from sales to their members, who are not necessarily part of the same geographical community. Other types of initiatives include community development companies or not-for-profit organizations who manage production or supply for direct local benefit Harnmeijer 2017, Harnmeijer et al 2018), and sustainability movements of various sorts ranging from substantial and well-organized transition towns initiatives (Seyfang and Haxeltine 2012) to eco-villages and informal citizen's groups emphasizing selfsufficiency and energy saving (Renau 2018, Zhu et al 2015, Georg 1999. However, as Creamer et al (2018) have observed, CE refers to a broad spectrum of energy-related initiatives, not a specific class of project.…”
Section: Community Energymentioning
confidence: 99%